2012
DOI: 10.1186/1471-2458-12-784
|View full text |Cite
|
Sign up to set email alerts
|

Who tended to continue smoking after cancer diagnosis: the national health and nutrition examination survey 1999–2008

Abstract: BackgroundIt has been estimated that there are approximately 12 million cancer survivors in the United States. Continued smoking after a cancer diagnosis is linked to adverse effects among cancer survivors on overall survival, treatment effectiveness, and quality of life. Little is known about who is more likely to quit smoking after his/her cancer diagnosis. The objective of this study is to evaluate factors associated with smoking cessation in cancer survivors, which to date has not been well studied.MethodT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 35 publications
4
77
2
1
Order By: Relevance
“…About 20% of current cancer patients in Canada are smokers. Similar conclusions have been reached in other studies showing that 20%-30% of cancer patients continue to smoke after their diagnosis [12][13][14] .…”
Section: Discussionsupporting
confidence: 91%
“…About 20% of current cancer patients in Canada are smokers. Similar conclusions have been reached in other studies showing that 20%-30% of cancer patients continue to smoke after their diagnosis [12][13][14] .…”
Section: Discussionsupporting
confidence: 91%
“…For smokers in an otherwise healthy population, females are less likely to try to quit smoking and more likely to relapse after trying to quit (Perkins, 2001; Piper et al, 2010; Ward, Klesges, Zbikowski, Bliss, & Garvey, 1997; Wetter et al, 1999). Literature is mixed regarding the sex-specific patterns of smoking cessation after diagnoses of a life-threatening illness (e.g., stroke, chronic obstructive pulmonary disease, and cancer) with support for equivalent, higher, and lower quit rates in males than females (Bak et al, 2002; Berg et al, 2013; Redfern, McKevitt, Dundas, Rudd, & Wolfe, 2000; Tashkin et al, 2001; Tseng, Lin, Moody-Thomas, Martin, & Chen, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of 566 individuals from the National Health and Nutrition Examination Survey (NHANES; ref. 7), cross-sectional analyses found that the likelihood of (self-reported) smoking post-diagnosis was associated with being female, younger, Hispanic, underweight or normal weight, and not having a smoking-related cancer. Other studies have corroborated findings regarding female gender (15) and younger age (15) and also documented lower income and/or education (16) and type of cancer (17) as predictors of quitting smoking post-diagnosis.…”
Section: Predictors Of Quitting Among Survivorsmentioning
confidence: 99%
“…Yet a significant proportion of cancer survivors continue to smoke tobacco post-diagnosis (3)(4)(5)(6)(7). Population-based, cross-sectional surveys estimate that between 15% and 18% of cancer survivors currently smoke (8)(9)(10)(11), but prevalence varies by type of cancer diagnosis (9,10) and is higher among younger survivors (8,10) and those diagnosed with smokingrelated cancers (11).…”
Section: Prevalence and Patterns Of Smoking In Survivorsmentioning
confidence: 99%